Pengaruh Bentonit Parit Melingkar Terhadap Nilai Resistans Pentanahan Satu Batang Pentanah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Grounding resistance of a ground rod depends on the type of soil condition, dimension and arrangement of the ground rod. Ground rod is more convenient than ground plate or ground strip. The value of grounding resistance must be as small as possible. It is difficult to reach the value of the grounding resistance that fulfils the standard. There are some ways or methods to reduce the grounding resistance, such as making parallel ground rod or applying soil treatment. Bentonite (A.1203.4Si02.H20) can be applied to reduce the grounding resistance, because it has a capability to absorb water. Bentonite contains water (H20) so that it is capable to maintain the ground humidity. The ground rods used in this experiment are cylinder rods with a length of 1 meter and diameter of 12.7 milimeters. The rod is dipped into the earth. One end of the rod is on the ground surface. The grounding resistance value of the rod without bentonite is compared with the grounding resistance value of the rod with circle trench bentonite. The depth and diameter of the circle trench bentonite were varied. The results showed that the grounding resistance value of one ground rod without bentonite was 164 ohms. The grounding resistance value of one ground rod with circle trench bentonite was 124 ohms untill 31 ohms. The decrement of the values of the grounding resistance with bentonite were 24 % to 81 %. These results agree with the IEEE Standard 141-1993. This standard state that the decrement values of the grounding resistance with chemical treatment are 15 % to 90 %. The grounding resistance value of one ground rod without bentonite is higher than that of with bentonite. If the value of circle trench width of bentonite was higher, the grounding resistance value was lower. If the value of circle trench depth of bentonite was higher, the grounding resistance value was lower.